Digital Leadership Agility as a Strategic Lever for Organizational Resilience in Multinational Corporations - Hermansyah, Heri; Zakaria, Ricky Muhamad; Abdurrohman (Novatio : Journal of Management Technology and Innovation, 2024)
The accelerating pace of digital transformation, globalization, and technological disruption underscores the importance of Digital Leadership Agility (DLA) in multinational corporations (MNCs). This study examines the influence of DLA on Organizational Resilience (OR) through strategic alignment and dynamic capabilities, while also considering the moderating roles of national digital competitiveness and organizational stagility.  A cross-sectional survey covering business units from multiple industries in the Asia-Pacific, European Union, and North America was conducted. Using validated measurement scales, the study applied Structural Equation Modeling (SEM) and Hierarchical Linear Modeling (HLM) to test mediation, moderation, and cross-cultural comparability. The results show that DLA significantly enhances OR through strategic alignment and dynamic capabilities, with stronger effects in high-technology industries. National digital competitiveness and organizational stagility further strengthen these relationships, indicating threshold effects of infrastructure and capability. The findings also highlight the relevance of organizational culture and resources, and emphasize the need to balance agility and stability. Practical implications include decentralizing decision making, fostering cross-functional collaboration, and tailoring leadership training to industry and cultural contexts. Overall, DLA emerges as a critical driver of OR by integrating digital transformation with adaptive leadership practices. Organizations should embed DLA in leadership development and design structures that balance responsiveness with cohesion. For policymakers, especially in digitally emerging economies, investing in leadership capacity, innovation ecosystems, and infrastructure is essential to enhance competitiveness and ensure sustainable growth.